Bioinformatics : Inference Of Population Genetic Structure Of Peninsular Malaysia Malay Sub-Ethnic Group Using Single Nucleotide Polymorphisms (SNPs) Microarray Multilocus Genotype Data - Wan Isa, Wan Nur Hatin (2012)
In Peninsular Malaysia, the Malays consist of various sub-ethnic groups which are believed to have different ancestral origins based on their migrations centuries ago. Knowledge of Malay population genetic structure is not just important for a proper design of biomedical studies, but also helpful in understanding their demographic histories of migration and admixture. This study was conducted with the aim of identifying and analyzing the genetic structures and ancestral membership coefficients of five Malay sub-ethnic groups namely Melayu Bugis, Melayu Jawa, Melayu Minang, Melayu Kedah, and Melayu Kelantan.